Biomechanical Role of Lateral Structures in Controlling Anterolateral Rotatory Laxity: The lliotibial Tract - Kittl,C; Williams,A; Amis,AA (OPERATIVE TECHNIQUES IN ORTHOPAEDICS, 2017)
Recent research, focusing on rotatory knee laxity, has intrigued the whole orthopaedic knee community. First popularized by Hughston et al, peripheral knee injuries at the time of cruciate ligament rupture have regained more and more recognition, which has led to a better understanding of these injuries. Recent research has been focused on anterolateral rotatory instability, especially regarding those structures that are responsible for the high-grade anterior subluxation of the lateral tibial plateau when damaged. Work at Imperial College London showed that the iliotibial tract (ITT) was the primary restraint to internal tibial rotation, especially the capsulo-osseous layer of the ITT, which contributed almost 25% of controlling a 5-Nm internal rotation torque at early flexion angles. However, due to the complex fiber arrangement, the functional anatomy of the ITT is difficult to understand. Thus, this article focuses on the involvement of the internal tibial rotation in restraining internal rotation and the pivot-shift phenomenon.